Enhancing Creativity and Collaboration in Story Writing for Elementary School Students through Project-Based Learning based on Illustrated Stories - Resti, Nadia; Wibowo, Setiawan Edi (Jurnal Pendidikan Progresif, 2024)
Enhancing Creativity and Collaboration in Story Writing for Elementary School Students through Project-Based Learning based on Illustrated Stories. Objective: This study aims to analyze the impact of project-based learning (PjBL) model on students' creativity and collaboration in writing short stories. Methods: Involving 58 fifth grade elementary school students, this study used a descriptive qualitative approach. Data collection techniques were designed to evaluate the impact of Project-Based Learning (PjBL) on creativity and collaboration. Story writing tests focused on students' ability to produce creative works, while observations were conducted to examine students' activities during the learning process. Interviews were aimed at exploring students' and teachers' perspectives on the implementation of PjBL. The use of these various techniques provided a comprehensive picture of the influence of PjBL on students' learning process. Findings: The results showed that the implementation of PjBL increased students' involvement in the learning process, fostered creativity through the exploration of ideas, and encouraged collaboration in groups. Students became more active in organizing storylines, creating unique characters, and exploring local cultural values. PjBL also provides opportunities for students to think critically, reflectively and take responsibility for their learning outcomes. Conclusion: It was found that the implementation of PjBL proved to be an effective learning model to improve students' creative and collaborative writing skills while creating meaningful learning experiences. Keywords: project based learning, creativity, collaboration, story writing.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024138